THE RELEASE OF FLUORIDE IONS OF BIOACTIVE RESIN IN THE SOLUTION OF LACTIC ACID AND ARTIFICIAL SALIVA - Dewi Puspitasari; Nadya Fatimah Alzahrah; Indri Indah Tari; Diana Wibowo; Rahmad Arifin; Renie Kumala Dewi; Sherli Diana (FKG Unlam, 2022)
Background: Bioactive resin can release fluoride ions when contact with oral environment. In the oral cavity, saliva and metabolic results of Streptococcus mutans namely lactic acid may affect the release of ions due to pH changes. Purpose: to analyse the release of fluoride ions of bioactive resin in the solution of lactic acid and artificial saliva. Methods: Forty-two specimens (diameter 15 mm x thickness 1 mm; n= 7/group fabricated with Activa™ Bioactive Restorative (Pulpdent). The specimen swere randomized into six 6 groups which immersed in lactic acid, artifial saliva and distilled water for 1 and 7 days in the incubator at 37oC. The number of fluoride ion release was measured using pH Meter (Lutron-208). Results: Two Way Anova test and Post Hoc Bonferonni test show there are significant differences among all group for lactic acid 1 day (6.37 ± 0.74), artificial saliva 1 day (1.30 ± 0.48), distilled water 1 day (3.78 ± 0.97), lactic acid 7 days (22.9 ± 0.81), artificial saliva 7 days (19.00 ± 0.81), distilled water 7 days (21.60± 1.01) ppm. Conclusion: The fluoride ion release of bioactive resin which immersed in lactic acid solution was higher than in artificial saliva immersion. Keywords: Artificial saliva, Bioactive resin, Fluoride ion release, Lactic acid